81 - BIBLIOGRAPHIC UPDATE ABOUT PROTOCOLS TO INSTITUTION FROM THE EMERGENCY CAR (Fiep Bulletin - online, 2011)
The emergency car is an room where they must be contain of shape sequenced all material and equipment necessary for emergency and emergencies care. Our objective in this study to identify the protocols for the establishment the emergency cars and analyze how the nurses should act in the organization and management of emergency cars. This is a bibliographic search held in electronic databases, using the words "cardiac arrest", "emergencies" and "nursing protocols". Were part of 10 research articles, which were divided into two categories: Cars emergency: objectives and protocols of organization and the importance of nurses in the organization and management of emergency cars. The results showed that to have a successful resuscitation depends partly on the availability and functionality of materials, drugs and equipment for resuscitation, which should be contained in an emergency car. The organization these cars must is based in line with the only internationally accepted protocol for this purpose, which is The code cart statement of the American Heart Association. Regarding the performance of nurse's in organizing and managing emergency car seen that this is of fundamental importance in the diagnosis of associated problems, as well as training the multidisciplinary team. Thus, we conclude that to ensure good service and reduce the weaknesses and differences in care provided to victims in emergency situations is required, beyond the training of the multidisciplinary team, standardization of emergency cars using protocols based on knowledge and experience of evidence-based medicine. This working method of consensus that faces serious patient care problems and priorities have shown a decrease in mortality, in complications, in failures and medical errors in emergency services.
Keywords: Cardiopulmonary Resuscitation; Emergencies; Nursing Protocols